Financial Behavior and Locus of Control: Key Factors in Understanding Financial Fraud Tendencies - Sugiyanto; Zuhanda, M. Khahfi; Jahara, Aini; Abdillah, Azrul; Nabilla, Vivi; Panjaitan, Ema Sari (Jurnal Manajemen dan Keuangan, 2025)
Fraud is a serious challenge and threat gacor slot faced by various institutions and organizations. Financial reporting fraud is relatively rare but has a greater impact on losses. Financial pressure, opportunities and rationalization drive individuals to engage in fraudulent behavior (fraud). This study aims to determine whether financial behavior and internal locus of control influence the gacor slot tendency toward financial fraud. A total of 401 village officials were sampled in Deli Serdang Regency and measured using multiple regression analysis. The results showed a negative influence of financial behavior and internal locus of control on financial fraud tendencies, contributing 25.8% simultaneously. The implications of this study are expected for village officials gacor slot should enhance their internal locus of control and establish healthy management of financial management, through training and workshops.